Biofilms formed on humic substances : response to flow conditions and carbon concentrations - Rodrigues, A. L. (2010)
Stream biofilms are exposed to dynamic conditions of flow velocity and organic carbon availability. Thus, the aim of this study was to investigate the response of biofilms formed with and without humic substances (HSs) to an increase in flow velocity (0.04–0.10 m s-1) and HSs concentration (9.7 ± 1.0 to 19.8 ± 0.4 mg L-1 C). The highest amount of biofilm, measured as volatile suspended solids and total countable cells, was observed at 0.10 m s-1 without HSs. The bacterial community composition of the biofilm with HSs was characterized by sequences with high similarities (≥97%) to the genus Dokdonella and to the genera Comamonas, Cupriavidus and, Ralstonia. Sequences retrieved from the biofilm without HSs presented high similarities (≥97%) to the genus Sphingomonas and the genus Nitrosospira. Experimental results suggested that the presence of HSs under different concentrations and flow velocities did not significantly enhance the cell density of biofilms but influenced its microbial composition.